Prevalence and psychological sequelae of sexual abuse among individuals with an intellectual disability: A review of the recent literature - Byrne, Gary (Journal of intellectual disabilities, 2018)
The impact of sexual abuse among those with an intellectual disability is an area in need of further research. The current article provides an in-depth narrative review of the sexual abuse literature relevant to individuals with an intellectual disability. The 29 articles included in this study focused on (a) the prevalence of sexual abuse, (b) the risk factors associated with this population, and (c) the psychological impact of abuse. The findings confirmed that children and adults with an intellectual disability are at a higher risk of sexual abuse than nondisabled peers. Research regarding risk factors is equivocal, with a range of possible factors indicated. Similarly, evidence suggests that there is no single diagnostic trajectory when dealing with the sequelae of sexual abuse among those with an intellectual disability. The article concludes by discussing recommendations for future research and development of policy around this area.